PENGARUH KOMUNIKASI, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS SOSIAL, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN PONOROGO - Kademin Kademin; Suwardi Suwardi; Herning Suryo Sardjono (JI@P, 2023)
The purpose of this study was to determine the effect of communication, leadership and organizational culture on the performance of employees of the Social Service, Women's Empowerment and Child Protection in Ponorogo Regency. This research is a survey research and is classified as explanatory research. The research was conducted at the Social Service for Women's Empowerment and Child Protection, Ponorogo Regency. The population in this study was 54 employees of the Social Service for Women's Empowerment and Child Protection, Ponorogo Regency, and all of them became samples. Data collection techniques using questionnaires and literature study. Data analysis technique using multiple linear regression. The results showed that communication had a positive and significant effect on the performance of employees of the Office of Social Affairs, Women's Empowerment and Child Protection in Ponorogo Regency with a p value of 0.004 < 0.05 Leadership had a positive and significant effect on the performance of employees of the Office of Social Affairs, Women's Empowerment and Child Protection in Ponorogo Regency with a p value 0.036 < 0.05. Organizational culture has a positive and significant effect on the performance of employees of the Office of Social Affairs,   Women's Empowerment and Child Protection in Ponorogo Regency with a p value of 0.013 < 0.05, Communication, leadership and organizational culture affect the performance of employees of the Office of Social Affairs, Women's Empowerment and Child Protection in Ponorogo Regency simultaneously with a p-value of 0.000 < 0.05.   Keywords: communication, leadership, organizational cultu